When a River Becomes a Border - Layio, Robi (Journal of Anthropological Films, 2022)
Blangoua subdivision is the main Cameroonian window on Lake Chad. The Chari river which flows into the lake at the top of this town determines the border with Chad. The socio-cultural and economic proximity maintained by the population residing around the riverbank makes a border obsolete and unrealistic. People go freely and forth, and take advantage of these socio-ethnic corridors to sneak between the two nationalities in order to seize the opportunities presented to them. Waldiga, as many others in this region has a life on both sides. He navigates this reality in his daily life as a university student in Chad.